Serología de títulos maternales de la enfermedad de Gumboro en pollos de carne en la región sur del Ecuador - Paz Gómez, Jimmy Ricardo (2023)
The immunity conferred by the mother to the progeny in birds is considered important for the fight against pathogens such as the infectious Bursitis virus that affects the immune system. The present research was carried out in order to establish the maternal immunological profile for Gumboro disease, in day-old meat chickens, 8 farms in the south of Ecuador were sampled, the same coming from different incubators in the country, 20 samples were collected for each incubator where 1 ml of blood was taken to obtain serum and perform the Indirect ELISA test (ID.vet). The results were obtained through the ID Soft program, showed that 96.75% of the titers of baby chickens were positive and 3.25% negative for maternal antibodies, with a maximum average of 10860 and a minimum of 702,25 being the average geometric title in the eight incubators of 4762 which is considered protective within the standard. The average coefficient of variation (CV) was 41% that evidences a good uniformity of maternal titles, it is concluded that the breeders of the different incubators of Ecuador provide passive protective immunity to the progeny of marketed chickens, it is important to know the origin and level of circulating maternal immunity in order to implement effective vaccination programs, in addition to frequently monitoring passive immunity and applying the Deventer formula, to predict a possible age-specific vaccination program with different types of vaccines. Keywords: Gumboro disease, maternal antibodies, Deventer formula, Indirect ELISA, meat chickens.